RESEARCH ON NUMERICAL SIMULATION OF STRESS DISTRIBUTION OF ANTI-TWIST BRAIDED WIRE ROPE - FU Chao; WANG Hui; CUI WeiHua; XU HongQin; ZHAO Xia (Jixie qiangdu)
Applying the differential geometry theory and principle of coordinate transformation,the spatial curve parametric equations were derived. An geometric entity model of the anti-twist braided wire rope was established using the three-dimension software. The finite element model of the anti-twist braided wire rope can be acquired by appropriate meshing operation. The boundary conditions are set after loading the constraints and the mass force. and the numerical simulation of the strand stresses deformation was conducted. Then the distribution laws of strand stress distribution and axial deformation in axis dire- ction in its cross section were obtained. Friction coefficients were set as different parameters to obtain the influence law of friction coefficients on strand stresses deformation. The calculation results of strand with five different pitch were analyzed and the influence law of pitch on the strand was obtained.